ANALISIS PERBANDINGAN KINERJA KEUANGAN DAN KINERJA PASAR PERUSAHAAN SEBELUM DAN SESUDAH AKUISISI PADA PT JASA MARGA (PERSERO) TBK PERIODE 2012 – 2018 - Anifah Aliwartaya; Saryadi Saryadi (Universitas Diponegoro, 2019)
The purpose of this study was to know the comparison of financial performance and financial market performance before and after the acquisition of PT Jasa Marga (Persero) Tbk for the period 2012 - 2018. The variables of this study were PT Jasa Marga Persero's financial performance and PT Jasa Marga Persero's market performance. The type of research was comparative with a quantitative approach. The data used in this research was secondary data which obtained from the Indonesia Stock Exchange website and the official website of PT Jasa Marga. The data analysis technique used normality tests, paired sample t-test, and multivariate analysis of variance test. The test result on financial performance variable showed a significance level 0,120 > 0.05. It meant that there was no significant difference between the financial performance before the acquisition and the financial performance after the acquisition. The test result on market performance variable showed a significance level 0,218 > 0.05. These results indicated that there was no significant difference between the market performance before the acquisition and the market performance after the acquisition.